COVID-19 impact on urban mobility - Mahmudur Rahman Fatmi (Journal of Urban Management, 2020)
This paper presents individuals' adjustment in daily out-of-home travel activities, in-home activities, and long-distance travel during the COVID - 19 travel restrictions. This study utilizes data from the COVID - 19 Survey for assessing Travel impact (COST) for the Kelowna region of British Columbia, Canada. The analysis suggests that individuals' participation in out-of-home activities were reduced by more than 50% during COVID - 19. The highest daily frequency of travel is found for routine shopping, followed by work-related travel. A comparative analysis of adjustment in out-of-home activities during COVID - 19 and the pre-pandemic period suggests that work-related travel increased for some occupations such as health, community, government, and sales and services. For recreational/social activities, travel increased for a higher share of older adults, and decreased for a higher share of younger adults. In the case of in-home activities, higher income households were found to be predominant in tele-working for a longer duration; whereas, lower and middle income groups were more involved in leisure and discretionary activities, and sleep. In the case of long-distance travel, the majority of the completed long-distance travel was made regionally using private car. Among the altered (i.e. cancelled, rescheduled, and unchanged) long-distance trips, international air-travel was predominant. The findings of this study provide insights towards people's immediate response to COVID - 19 travel restrictions, which will help in developing transportation plans and policies during COVID - 19, as well as for future pandemic and any other unprecedented scenarios.
Keywords: 710; COVID-19; In-home activity; Long-distance travel; Out-of-home travel activity